The Role of Skadron-12/Serbu Puspenerbad in Supporting Gatot Soebroto Airport Activation - Aulia, Elfaz Faqih; Armawi, Armaidy; Waluyo, Joko; Wahidin, Darto (Nusantara Science and Technology Proceedings, 2021)
The paper purpose is to describe the roles, challenges, and strategies of Skadron-12 or Serbu Puspenerbad in supporting the activation acceleration of Gatot Soebroto Airport in the Way Kanan Regency, Lampung. Skadron-12 or Serbu Puspenerbad must pay attention to the improvement system as mandatory. The security of the Gatot Soebroto Airport area in Way Kanan Regency must provide significant advantages. The need for existing human resources in Indonesia plays a vital role in maintaining the defense force and overcoming national problems. The presence of Skadron-12 or Serbu Puspenerbad in support of the Gatot Soebroto Airport activation. Part of Tentara Nasional Indonesia preparedness in handling potential national crises. Considering Indonesia's geography condition as an archipelagic nation, the Skadron-12 or Serbu Puspenerbad mode upgrading is necessary to empower the defense area. Such as the one at Gatot Soebroto Airport in Way Kanan Regency, Lampung. Activation upgrading support at Gatot Soebroto Airport is also can be used to address other non-military threats. The obstacles faced by Skadron-12 or Serbu Puspenerbad in the activation effort of Gatot Soebroto Airport, including lack of equipment quality and availability, ideal-deviated flight conditions phenomena and problems, and low intensity in infrastructure maintenance. Hence, strategies used to support activation acceleration implementation involve three things. Those are knowledge improvement of flight safety procedures, flight safety procedures supporting training development, and flight safety procedures supporting facility updates. Thus, the formed strategy development was operated to answer every obstacle and aviation problem faced by Skadron-12 / Serbu Puspenerbad in Gatot Soebroto Airport activation located in Way Kanan Regency, Lampung.